2011
DOI: 10.1007/s00436-011-2558-2
|View full text |Cite
|
Sign up to set email alerts
|

Anthelmintic effect of a methanol extract of leaves of Dregea volubilis on Paramphistomum explanatum

Abstract: Dregea volubilis (family Asclepediaceae) is widely used as anthelmintic in traditional system of medicine in eastern and southern part of India. The aim of this study was to evaluate the anthelmintic activity of the methanol extract of D. volubilis leaves (MEDV) and to observe its effect through SEM study. Live parasites (trematode Paramphistomum explanatum) were collected from buffalo in 0.9% phosphate-buffered saline (PBS). It was incubated at 37 ± 1°C in media containing either no extract (control), the tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 22 publications
0
25
1
Order By: Relevance
“…Various studies on in vitro and in vivo anti-trematodal activity of medicinal plants viz., alcoholic extract of Allium sativum and Piper longum [58], Balanites aegyptica [17], bark of Prosopis cineraria [18], Plumbagin on Fasciola gigantica and Paramphistomum cervi [37,59], 50 medicinal plants against Schistosoma mansoni and Echinostoma caproni used in Côte d' Ivoire [16], Bombax malabaricum leaves against Paramphistomum explanatum [15], Dregea volubilis leaves against Paramphistomum explanatum [60], Artemisia annua, A.absinthium, A.siminatriloba and Fumaria officinalis against adult Schistosoma mansoni, Fasciola hepatica and Echinostoma caproni in vitro [14], Aegle marmelos, Andrographis lineata, A.paniculata, Cocculuc hirsutus, Eclipta prostrata and Tagetes erecta against Paramphistomum cervi [13], Flemingia estita root tuber against Paramphistomum sp. [9].…”
Section: Discussionmentioning
confidence: 99%
“…Various studies on in vitro and in vivo anti-trematodal activity of medicinal plants viz., alcoholic extract of Allium sativum and Piper longum [58], Balanites aegyptica [17], bark of Prosopis cineraria [18], Plumbagin on Fasciola gigantica and Paramphistomum cervi [37,59], 50 medicinal plants against Schistosoma mansoni and Echinostoma caproni used in Côte d' Ivoire [16], Bombax malabaricum leaves against Paramphistomum explanatum [15], Dregea volubilis leaves against Paramphistomum explanatum [60], Artemisia annua, A.absinthium, A.siminatriloba and Fumaria officinalis against adult Schistosoma mansoni, Fasciola hepatica and Echinostoma caproni in vitro [14], Aegle marmelos, Andrographis lineata, A.paniculata, Cocculuc hirsutus, Eclipta prostrata and Tagetes erecta against Paramphistomum cervi [13], Flemingia estita root tuber against Paramphistomum sp. [9].…”
Section: Discussionmentioning
confidence: 99%
“…A number of drugs have been assessed and recommended for the treatment of paramphistomosis (Panyarachun et al 2010;Rolfe and Boray 1988). It was reported earlier by our group that the methanol extract of leaves of Dregea volubilis was effective against P. explanatum (Hossain et al 2011b). Interestingly enough, it was found that different plants do possess anthelmintic activity (Agaie and Onyeyili 2007;Aswar et al 2008;Ferraz et al 2010;Mehlhorn et al 2011;Roy and Swargiary 2009;Schmahl et al 2010;Tandon et al 1997;Yadav and Tangpu 2009).…”
Section: Introductionmentioning
confidence: 97%
“…Several studies proved that different plant extracts have significant killing effects in vitro and in vivo on nematodes, cestodes, and trematodes Klimpel et al 2011;Abdel-Ghaffar et al 2011). Hossain et al (2011 evaluated the anthelmintic activity of the methanol extract of Dregea volubilis leaves against Paramphistomum explanatum and observed its effect through SEM study.…”
Section: Introductionmentioning
confidence: 99%